Implementation of a User-Centric Context-Aware Playground - Lau, Sian Lun; Klein, Niklas; Pirali, Andreas; König, Immanuel; David, Klaus (Electronic Communications of the EASST, 2009)
Since the introduction of the ubiquitous computing vision by Mark Weiser, we observed quite some research from various R&D projects as well as groups that focused on different aspects in the area of context-awareness. However, there is yet no result which we can easily apply in a real environment. The context-aware service development and deployment process seldom focused on reusability and realistic implementation issues. We believe these issues can be tackled by proposing a complete context-aware system package. In this package both developers and users will be supported. This idea is realised at our department as a context-aware playground. This paper explains the observation on current work and the shortcomings, and proposes how the context-aware playground approach can be a solution.